2006
DOI: 10.1007/s00234-006-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous gadolinium-DTPA on diffusion-weighted imaging

Abstract: Contrast medium injection had significant and time-dependent effects on ADC values. Therefore, only pre-contrast and late DW images should be used in quantitative ADC studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 15 publications
6
35
3
Order By: Relevance
“…The effect of contrast agent at diffusion-weighted imaging has been discussed in several studies (58)(59)(60)(61)(62). The majority of studies show a tendency for the ADC value to decrease after contrast enhancement, although this decrease was not statistically significant in some studies (58)(59)(60)(61)(62).…”
Section: Influence Of Contrast Agent At Diffusion-weighted Imagingmentioning
confidence: 96%
“…The effect of contrast agent at diffusion-weighted imaging has been discussed in several studies (58)(59)(60)(61)(62). The majority of studies show a tendency for the ADC value to decrease after contrast enhancement, although this decrease was not statistically significant in some studies (58)(59)(60)(61)(62).…”
Section: Influence Of Contrast Agent At Diffusion-weighted Imagingmentioning
confidence: 96%
“…Yamada et al found a significant decrease of the ADC value after CM administration [20], while there was no difference in the study of Fitzek et al [21]. In the study of Yamada et al, DWI was obtained immediately after CM application, while there was a longer time interval in the study of Fitzek et al Firat et al combined both protocols and found a significant decrease of the ADC value of normal brain tissue and infarct immediately after CM application which normalized in the late post-contrast DW images [22]. They explained this phenomenon as an effect of the intravascular CM on the diffusion-weighted images.…”
mentioning
confidence: 99%
“…. .,'' none of their data were acquired with T2*-sensitive sequences and apparently the mechanisms relating T2* changes to ADC alterations have not been appreciated in either their work or the previous pre-postcontrast studies in neurological applications (2,3). Additional experimentation is required before definitive conclusions regarding the mechanisms for observed ADC reductions following Gd contrast in high uptake lesions is warranted.…”
mentioning
confidence: 99%